Learning Design In Improving Learning Outcomes Using Visual Media And Audio Visual On Beautiful Materials Respect Mutual Respect - Husni; Wahab (IJGIE (International Journal of Graduate of Islamic Education), 2023)
process of achieving learning outcomes. The research method uses qualitative methods with the type of Classroom Action Research (CAR). Primary data source; teacher of Islamic Religious Education, and students of class VI SDN 02 Nobal. The results of this study indicate that student learning outcomes in the beautiful material of mutual respect in Islamic Religious Education subjects during the application of visual and audio-visual media experienced an increase as seen from the average score before learning was 73.3% after using audio-visual press media learning outcomes in the first cycle it increased with an average value of 79.1% and in the second cycle it reached 84.5%. So that using visual and audio-visual media can improve the learning outcomes of class VI students in the subject of Islamic Religious Education in the beautiful material of mutual respect at SDN 02 Nobal.